Benarkah Yusuf dan Zulaikha Menikah? Analisa Riwayat Isra’iliyyat dalam Kitab Tafsir - Ali Mursyid; Zidna Khaira Amalia (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
This article investigates the narration of isrāiliyyāt in the story of the Prophet Jusuf (Joseph) and Zulaikha,  the wife of Al-Aziz who bought the Prophet Jusuf from the hand of the traveler of Egypt. The results of this study are: firstly, the narration related to the name of Al-Aziz as Qiṭfir or Iṭfir and the name of his wife as Zulaikha or Ra’il. This narration according to the Qur’anic interpreters was not based on the Qur’an and Prophetic Sunna. Although this version of narration will not influence  ‘aqīdah of Muslim society, it should be avoided. Secondly, narration related to a temptation of the wife of Al-Aziz to the Prophet Jusuf which also presented by the interpreters of the Qur’an. According to them, the version is untrue because it is impossible that the Prophet Jusuf did a cruel deed such that the version can damage ‘aqīdah of Islamic society. Thirdly, according to the interpreters of the Qur’an, the narrations on the marriage of the Prophet Jusuf to Zulaikha is not based on the Qur’an and the authentic Hadith.